2019
DOI: 10.1042/bsr20190954
|View full text |Cite
|
Sign up to set email alerts
|

Association between PTEN and clinical-pathological features of osteosarcoma

Abstract: Previous studies indicated the prognostic value of phosphatase and tensin homolog deleted on chromosome ten (PTEN) in osteosarcoma (OS). There was a great degree of inconsistency between these reports. The aim of this meta-analysis was to investigate the clinicopathological features and prognostic role of PTEN positive expression on OS. We searched NCBI PubMed, Embase, Springer, ISI Web of Knowledge, the Cochrane library, China National Knowledge Internet database (CNKI), Wanfang database, Chinese VIP database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Consequently, PTEN may act as a crucial regulator in OS progression. It was reported that PTEN expression was negatively associated with OS metastasis and survival ( 28 ). Besides, Blüml S showed that PTEN (-/-) displayed increased osteoclast number and bone resorption, indicating the negative regulation of osteoclastogenesis and function by PTEN ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, PTEN may act as a crucial regulator in OS progression. It was reported that PTEN expression was negatively associated with OS metastasis and survival ( 28 ). Besides, Blüml S showed that PTEN (-/-) displayed increased osteoclast number and bone resorption, indicating the negative regulation of osteoclastogenesis and function by PTEN ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its loss or deactivation has been reported in the development of osteosarcoma. 35,36 Many noncoding RNAs have been identified, which can bind to PTEN, such as circ-ORC2 and miR-19a 37 and miR-29. 38 An increasing number of studies have shown that PTEN/ PI3K/Akt pathway is involved in the tumorigenesis of osteosarcoma as the loss of function of PTEN may prevent the phosphorylation of PIP2 and decrease the PIP3 and eventually activate the PI3K-Akt pathway to inhibit cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…There are other less frequent alterations, such as FGFR1, which, as demonstrated by Amary et al in 288 patients, occurs in up to 18.5% of patients and is associated with a worse response to chemotherapy and, therefore, a worse prognosis [ 39 ]. On the other hand, there are good prognostic factors, such as PTEN, which was highlighted by Zhou et al in a review of 13 articles that included 580 patients with osteosarcoma; a positive expression of PTEN was associated with a better prognosis, including a lower incidence of metastasis and larger differentiated tumours, which were, therefore, less aggressive [ 40 ]. We have previously noted that there is a difference between osteosarcoma in adults and in children, where the most frequent alterations in both cases are alterations in the expression of the p53 and Rb genes.…”
Section: Genetic Markersmentioning
confidence: 99%